Effects of the technology acceptance model on attitude and behavioral intention: Evidence from physicians in secondary-level hospitals on Java Island - Setiawan, Eka; Syah, Tantri Yanuar Rahmat; Hamdi, Edi; Dewi, Sandra (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the factors influencing doctors’ adoption of Electronic Medical Records (EMR) in secondary-level hospitals in Java, Indonesia. Drawing on the Technology Acceptance Model (TAM) and Resource-Based Theory (RBT), the research examines how perceived usefulness, perceived ease of use, technology self-efficacy, outcome expectation, and discomfort shape doctors’ attitudes, behavioral intentions, and actual EMR use. A causal research design was employed, surveying 400 doctors from 80 secondary-level hospitals. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypothesized relationships. The findings reveal that TAM significantly predicts doctors’ attitudes and behavioral intentions, which in turn strongly influence actual system use. Conversely, moderating factors such as technology self-efficacy and outcome expectation did not significantly impact adoption, while initial discomfort did not hinder engagement, suggesting adaptive coping among physicians. The study concludes that perceptions of system usefulness and ease of use are the primary drivers of EMR adoption, overshadowing individual confidence or anticipated benefits. Practically, the results highlight the importance of user-friendly system design, hands-on training, and supportive institutional culture to enhance adoption. These insights offer actionable guidance for hospital administrators and policymakers aiming to improve digital transformation and operational efficiency in healthcare.